New edition chemistry - Harwood, Richard (Cambridge University Press Cambridge, 2003)
Chemistry - New Edition matches the Cambridge International Examinations syllabuses for IGCSE and O Level Chemistry. It is also suitable for use with all UK GCSE Specifications. The text is clearly separated into core and extension material, with questions at the end of each section to test understanding. General material includes revision guidance, past examination questions with answers and a glossary of key terms. The accessible language and extensive use of high-quality colour illustrations ensure that the material is suitable for all students, including those for whom English is not their first language.